Kosa Pan: The Ambassador Who Saved the Kingdom - Chantang, Doungrak (FOYER: The Journal of Humanities, Social Sciences, and Education, 2024)
Kosa Pan: The Ambassador Who Saved the Kingdom by Phuthorn Pumathorn is a historical account detailing the background of Phraya Kosa Thibodi (Pan), the extraordinary envoy and royal ambassador who embarked on diplomatic missions to foster bilateral relations with the French government during the reign of His Majesty King Narai the Great. Presenting the narrative of Phraya Kosa Thibodi (Pan) from various crucial documents, both Thai and international, particularly those from France, this book enhances readers’ familiarity with this distinguished ambassador. Not only did Phya Kosa Thibodi (Pan) serve as an ambassador extending royal messages, but he also engaged in diplomatic negotiations adeptly. This, in turn, enabled Westerners to gain a deeper understanding of the Kingdom of Siam and acknowledge the cultural sophistication of the Siamese people. The book is structured to provide insight into this remarkable figure, shedding light on his multifaceted role as a diplomat.